2023
DOI: 10.1021/jacs.2c13648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Radical-Induced Selective Oxidation of Methane over Nonmetallic Boron Nitride Catalysts

Abstract: Boron-based nonmetallic materials (such as B2O3 and BN) emerge as promising catalysts for selective oxidation of light alkanes by O2 to form value-added products, resulting from their unique advantage in suppressing CO2 formation. However, the site requirements and reaction mechanism of these boron-based catalysts are still in vigorous debate, especially for methane (the most stable and abundant alkane). Here, we show that hexagonal BN (h-BN) exhibits high selectivities to formaldehyde and CO in catalyzing aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
(104 reference statements)
0
15
1
Order By: Relevance
“…In path-D, the formation of HOO species is shown which is not in line with the experiment [26] available in literature. Hence, the occurrence of path-D during the methane oxidation is minimal.…”
Section: Path-d (Interaction Of O 2 With Bà Ooh Unit In Zigzag-booh)contrasting
confidence: 67%
See 3 more Smart Citations
“…In path-D, the formation of HOO species is shown which is not in line with the experiment [26] available in literature. Hence, the occurrence of path-D during the methane oxidation is minimal.…”
Section: Path-d (Interaction Of O 2 With Bà Ooh Unit In Zigzag-booh)contrasting
confidence: 67%
“…In an in-situ synchrotron vacuum ultraviolet photoionization mass spectroscopy experiment available in the literature, [26] it was revealed that HOO radical formation does not take place in this reaction. Hence, path-C which demonstrates the presence of HOO radical, is not in-line with the experimental observation.…”
Section: Path-c (Interaction Of O 2 With Bà Oh Unit In Zigzag-boh)mentioning
confidence: 99%
See 2 more Smart Citations
“…Methane is a key energy carrier in the transition to sustainable production of fuels and chemicals. Most approaches for methane utilization involve successive C–H bond cleavages to form surface carbons that are removed by co-reactant-derived oxygen species; these routes include steam and dry reforming (H 2 O or CO 2 as co-reactant ), partial oxidation (O 2 as co-reactant ), and autothermal reforming into CO x and H 2 , the simplest building blocks that can be converted into a wide variety of carbon-containing products. Strategies have also been devised for direct selective C–H bond activation of methane into functionalized compounds that may be further upgraded (including halogenations, oxidative coupling, and partial oxidation ).…”
Section: Introductionmentioning
confidence: 99%